Economic gangsters : corruption, violence, and the poverty of nations - Fisman, Raymond; Miguel, Edward (Princeton, New Jersey : Princeton University Press, 2010)
Meet the economic gangster. He's the United Nations diplomat who double-parks his Mercedes on New York City streets at rush hour because the cops can't touch him--he has diplomatic immunity. He's the Chinese smuggler who dodges tariffs by magically transforming frozen chickens into frozen turkeys. The dictator, the warlord, the unscrupulous bureaucrat who bilks the developing world of billions in aid. The calculating crook who views stealing and murder as just another part of his business strategy. And, in the wrong set of circumstances, he might just be you. In Economic Gangsters, Raymond Fis.
Cover; Title; Copyright; Contents; Chapter One: Fighting For Economic Development; Chapter Two: Suharto, Inc.; Chapter Three: The Smuggling Gap; Chapter Four: Nature or Nurture? Understanding the Culture of Corruption; Chapter Five: No Water, No Peace; Chapter Six: Death by a Thousand Small Cuts; Chapter Seven: The Road Back From War; Chapter Eight: Learning to Fight Economic Gangsters; Epilogue: Doing Better This Time; Postscript to the Paperback Edition; Acknowledgments; Notes; Index.
Originally published: 2008.
Online resource; title from digital title page (viewed on December 05, 2018).
eBooks on EBSCOhost
Keywords: Corruption -- Economic aspects; Political corruption -- Economic aspects; Economic development; Violence -- Economic aspects; Smuggling; Corruption -- Aspect économique.; Corruption (Politique) -- Aspect économique.; Développement économique.; Violence -- Aspect économique.; Contrebande; economic development; TRUE CRIME -- General; BUSINESS & ECONOMICS -- Business Ethics; Violence -- Economic aspects; Economic development; Political corruption -- Economic aspects; Smuggling